Scales for rating the behavioral characteristics of superior students: a preliminary examination of the psychometric properties of the Greek version of the first four scales: learning, creativity, motivation, and leadership scale - Rachanioti, Eleni; Foti, Theodora; Geitona, Aikaterini Rafaella; Tzalla, Anastasia; Dougali, Anna; Fragkomichelaki, Olga; Bourmpou, Christina; Staikopoulou, Maria; Papantoniou, Aphrodite; Varlami, Fotini; Dinaki, Irene; Tsiountala, Maria; et al. (Frontiers in Education, 2025)
The Scales for Rating the Behavioral Characteristics of Superior Students (SRBCSS; Renzulli et al., 2010) are notable for incorporating teachers’ informed evaluations in identifying gifted students. Teachers’ close interactions with students enable them to make meaningful judgments, and the SRBCSS provides a structured method to guide and strengthen their nominations. The aim of the present study was to gain insight into the psychometric properties of the Greek version of the first four Scales for Rating the Behavioral Characteristics of Superior Students (SRBCSS), which assess various dimensions of giftedness. One hundred and forty-five (145) Greek primary and secondary education school (elementary and middle school) teachers completed the Learning, Creativity, Motivation, and Leadership scales of the SRBCSS to estimate the corresponding dimensions of giftedness in their students. Specifically, 145 students (83 girls and 62 boys) were evaluated by their teachers. The unidimensional structure of each of the aforementioned SRBCSS scales was tested using exploratory (EFA) and confirmatory (CFA) factor analyses, both of which demonstrated their one-factor structure. CFA analysis also confirmed their content validity, as all four scales were found to be positively correlated at statistically significant levels in the structural model. Furthermore, the number of underlying factors (latent variables) in their total organization was also examined using CFA at scale-level data. Both the one-factor and the correlated two-factor models’ solutions demonstrated statistically equivalent, excellent fit. Additionally, the internal consistency reliability of the four scales was evaluated with Hancock’s H coefficient and found to be good to excellent for all of them. Furthermore, moderate correlations were found between the first four scales of SRBCSS and the GRS-S scales, thus supporting their convergent validity. The research findings indicate that the specific SRBCSS scales can be used as reliable and valid tools for identifying gifted students (by their teachers) in the Greek educational context.